Antecedents of Repurchase Intention on Livehaf Fashion Brand in Mobile Online Shopping Apps - Arinta Daniswara; Budi Astuti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The rapid development of technology has encouraged several companies to create online business strategies using mobile online shopping applications. This makes competition increasingly fierce between companies. This study aims to examine the factors that trigger repurchase intention at the fashion brand Livehaf in the mobile online shopping application tiktok shop which consists of customer engagement, brand loyalty, and customer equity (brand equity, value equity, and relationship equity). This study uses a quantitative approach with a questionnaire to obtain primary data through the Google Form. The number of respondents in this study amounted to 180 respondents. Then it is processed using the SEM method through the SPSS and PLS-SEM applications with the SmartPLS device. The results of this study indicate that customer engagement has a positive and significant effect on customer equity and brand loyalty. In addition, value equity, relationship equity, and brand loyalty also have a positive and significant effect on repurchase intention. However, there is no relationship between brand equity and repurchase intention. This study contributes to adding to the marketing literature related to repurchase intention on mobile online shopping applications. This study also adds references to marketing managers to manage constraints that can influence potential customers repurchase decisions which can increase sales.